Age-Related Anatomical and Morphological Development of the Ruminant Stomach in Kids - Ersek, Adel; Mireşan, Vioara; Miclea, Mihai; Pusta, Dana (Acta Agraria Debreceniensis, 2001)
We observed the anatomical and morphological development of each compartment of the ruminant stomach in 3. 6. and 14 week old kids. Weaning from milk to roughage foraging, depending on the kids’ ages, stimulated the development of the rumen and reticulum, and decreased the abomasum portion. A 3 week old kid’s rumen has dense and thin papillas but, with advancing age and with roughage foraging, the number of the papillas on cm2 decreases and their width increases. The omasum tertiary laminae and especially the quaternary laminae are observable only in the advanced age categories.